Implementasi Digital Marketing untuk Peningkatan Pengunjung Usaha Garasi Poncol - Dwi Prayoga; Isram Rasal (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study explores the application of digital marketing strategies to enhance business performance, using a case study of Garasi Poncol. The research focuses on the implementation of a website program within the context of digital marketing for a used car trading business. The Garasi Poncol website was developed by the author with support from the Kampus Merdeka MSIB program. The objective of this study is to understand how the Garasi Poncol website was designed and implemented to increase exposure and sales of used cars through effective digital marketing strategies. The research method employed is a case study, examining the development of the Garasi Poncol website from inception to launch, along with the steps taken to promote and optimize the site. The results indicate that collaboration between the author and MSIB facilitated the creation of a website that meets business needs by incorporating various digital marketing features and techniques. These findings offer valuable insights for entrepreneurs and web developers on leveraging online platforms to grow and promote their businesses.